An intrinsic tonoplast protein of protein storage vacuoles in seeds is structurally related to a bacterial solute transporter (GIpF). - Johnson, K D (1990)
The tonoplast mediates the transport of various ions and metabolites between the vacuole and cytosol by mechanisms that remain to be elucidated at the molecular level. The primary structure of only one tonoplast protein, the H(+)-ATPase, has been reported to date. Here we report the primary structure of tonoplast intrinsic protein (TIP), a 27-kilodalton intrinsic membrane protein that occurs widely in the tonoplasts of the protein storage vacuoles (protein bodies) of seeds [Johnson, K.D., et al. (1989). Plant Physiol. 91, 1006-1013]. Hydropathy plots and secondary structure analysis of the polypeptide predict six membrane-spanning domains connected by short loops and hydrophilic, cytoplasmically oriented N- and C-terminal regions. TIP displays significant homology with several other membrane proteins from diverse sources: major intrinsic polypeptide from bovine lens fiber plasma membrane; NOD 26, a peribacteroid membrane protein in the nitrogen-fixing root nodules of soybean; and interestingly, GIpF, the glycerol facilitator transport protein in the cytoplasmic membrane of Escherichia coli. Based on the homology between TIP and GIpF and the knowledge that the protein storage vacuolar membrane and the peribacteroid membrane are active in solute transport, we propose that TIP transports small metabolites between the storage vacuoles and cytoplasm of seed storage tissues.